Is the Creation under Destruction?: Abraham Kuyper and Herman Bavinck on New Creation - Kristanto, David (Veritas : Jurnal Teologi dan Pelayanan, 2020)
Perhaps there is no better time to reflect on the new creation than now, amid the Covid-19 pandemic. All aspects of human life are being impacted by the pandemic, not to mention the danger of death that it generates. This critical situation brings out legitimate questions to the current state of the world (or creation): whether it is perishing, being abandoned by God, or whether God is punishing the world into destruction due to its abundance of sin. Attempting to answer those questions, the author will argue alongside Kuyper and Bavinck that God would never abandon nor destroy his creation. Even though corrupted by sin, God has no intention to destroy the creation; instead, he intends to restore it according to his original plan. God’s intention is not just to redeem the elect but to redeem the whole creation, and that complete redemption will find its fulfillment in the new creation. Such a reflection would encourage the Christian proclamation that God’s salvation extends to all creation.